Two dimensional PMMA nanofluidic device fabricated by hot embossing and oxygen plasma assisted thermal bonding methods. (7th May 2015) - Yin, Zhifu; Sun, Lei; Zou, Helin; Cheng, E
Abstract: A method for obtaining a low-cost and high-replication precision two-dimensional (2D) nanofluidic device with a polymethyl methacrylate (PMMA) sheet is proposed. To improve the replication precision of the 2D PMMA nanochannels during the hot embossing process, the deformation of the PMMA sheet was analyzed by a numerical simulation method. The constants of the generalized Maxwell model used in the numerical simulation were calculated by experimental compressive creep curves based on previously established fitting formula. With optimized process parameters, 176 nm-wide and 180 nm-deep nanochannels were successfully replicated into the PMMA sheet with a replication precision of 98.2%. To thermal bond the 2D PMMA nanochannels with high bonding strength and low dimensional loss, the parameters of the oxygen plasma treatment and thermal bonding process were optimized. In order to measure the dimensional loss of 2D nanochannels after thermal bonding, a dimension loss evaluating method based on the nanoindentation experiments was proposed. According to the dimension loss evaluating method, the total dimensional loss of 2D nanochannels was 6 nm and 21 nm in width and depth, respectively. The tensile bonding strength of the 2D PMMA nanofluidic device was 0.57 MPa. The fluorescence images demonstrate that there was no blocking or leakage over the entire microchannels and nanochannels.